Soapwort extract supplementation alters antioxidant status of serum, liver and heart tissues in growing Japanese quails reared under chronic intermittent cold stress - Dalkilic, Bestami; Ozcelik, Mehtap; Cambay, Zafer; Alayunt, Naci Omer; Simsek, Ulku Gulcihan; Mutlu, Seda Iflazoglu; Ciftci, Mehmet (Veterinarni A Farmaceuticka Univerzita Brno, 2017)
Antioxidant effect of dietary soapwort extract supplementation was studied in growing Japanese quails suffering from chronic intermittent cold stress. For this purpose, a total of ninety 15-d-old quails were divided into three groups with three replicates. Chronic intermittent cold stress was applied every night between 22.00 to 06.00 h; starting at 14 degrees C for the first week, and gradually weekly lowered to 8 degrees C. Three groups were fed with corn-soy based standard diets supplemented with 0, 50, and 100 ppm soapwort extract for four weeks. At the end of the study, three males and three females were slaughtered to determine total antioxidant and oxidant status of serum, malondialdehyde, glutathione, glutathione peroxidase activity, superoxide dismutase of liver and heart tissues. Although the dietary soapwort extract had no effect on serum total antioxidant capacity, it significantly lowered the total oxidant status of serum in cold stressed quails. Glutathione and superoxide dismutase enzyme activity of liver and heart tissues were similar among groups. While the dietary soapwort extract had no effect on glutathione peroxidase activity of the heart tissue, it significantly increased glutathione peroxidase activity in the liver tissue. In relation to the control group, malondialdehyde concentrations in the liver and heart tissues were significantly lower in soapwort extract groups. These data suggest that dietary soapwort extract could alleviate the detrimental effects of oxidative stress in growing Japanese quails exposed to cold stress.
Keywords: Malondialdehyde; glutathione peroxidase; saponin; total antioxidant status; total oxidant status